(untitled) (Afaq Lughawiyyah, 2023)
The twentieth century has witnessed a development in the concept of Language and Criticism. The French Linguist fardinand sorcer is one of the predecessors who brought revolution in the science of language and literature as he distinguished between language and Speech and differentiated between the system of language and literature which led to a new concept of Structure system, or construction. Indeed, the structural arrangement is among the most important cause of this development it is observed that the Classical Arabic critics have contributed immensely to structural criticism before him. Indeed, efforts of qudamah Bn ja’far al- Baqdadi in his book "poem criticism" is one of the first attempt in the concept of structuralism and from there abdul Qadr Aljurjany derived the structural terms such coherence and arrangement in some of his publications and books, just as many findings have emerged on structure, arrangement on Arabic poems. After him, hazim al- Qurtahani has researched on sentence structure and Rolern Bert followed al- jurjani and Qurtahani in their research and agreed equally to their postulates on structuralism. In the modern day, Ibrahim Anis with his students have played an active role in this topic and discussed structuralism in an acceptable form. In this paper, we shall present the definition of structuralism in brief and we shall mention some of its proponent and we shall discuss structuralism in literary criticism alongside its components as presented by the Arab Critics and the non-Arab critics and state the Islam perspective of it examining the artistic and the mastic aspects in details. In conclusion, we shall bring suggestions and advises citing references and sources which are external and internal.